Chronic non-communicable diseases and their impact on post-Covid-19 public health - Silva , Sarytha Edith Harrys de Lemos dos Santos; Oliveira , Camila Gabriele Santos de; Santana, Daniel; Lima , Mayara conceição Carmo de; Santos, Ana Beatriz Miranda dos; Oliveira, Milena Maria Andrade de; Silva, Mirela Claudia da; Nascimento, Marcia Natali do; Silva, Juliana Gomes da; Silva, Alex José Moreira da (Seven Editora, 2023)
The outbreak of the disease COVID-19 caused by the new coronavirus SARS-CoV-2, the WHO classified as an international pandemic, given the number of countries in which it was already registered. The virus coverage and restriction measures employed were to reduce the movement of people and effect social isolation, making it difficult to contact and group people. The relocation of primary health care professionals to provide care for COVID-19, the closure of outpatient clinics are reasons that negatively affected the medical follow-up for patients with Chronic Non-Communicable Diseases (NCDs). The objective of this work was to carry out a bibliographical survey of articles in online databases from 2019 to 2023 that addressed the chosen theme: CHRONIC NON-COMMUNICABLE DISEASES AND THEIR IMPACT ON PUBLIC HEALTH POST-COVID-19. This work is a bibliographic review of the literature extracted from the online database Scientific Electronic Library Online (SCIELO), Latin American and Caribbean Literature in Health Science (LILACS), Virtual Health Library (BVS) between 2019 to 2023. A new reclassified Action Plan was released, with an open Public Consultation focused on evaluating the Strategic Action Plan for Combating Chronic Diseases and Non-Transmissible Diseases in the country in the period 2021-2030. Patients with CNCD have greater use of health systems. Thus, it is essential that health environments, together with government officials, practice effective actions for the assistance of CNCD patients. DOI:https://doi.org/10.56238/sevened2023.006-023